Experimental study on soil impermeability based on chemical improvement method - Hai Sang; Bin Xiong; Chuan Jin; Deying Tang; Neng Xiong; Yifan Chen (PLoS ONE, 2025)
To address the challenge of high permeability in coastal silty sand foundation pits, which is prone to seepage failure, this study investigated the improvement effects of three chemical stabilizers—sodium silicate, calcium lignosulfonate, and sodium polyacrylate—on the permeability characteristics of undisturbed silty sand using a self-designed seepage test system. The results demonstrated that the cumulative erosion mass of the untreated soil increased exponentially over time, with an erosion rate as high as 89.39 g/min. In contrast, the cumulative erosion mass of the silty sand treated with any of the three chemical stabilizers exhibited a trend of initial increase followed by stabilization, and the erosion rates were all reduced to below 30 g/min. Notably, under the conditions of 4% dosage and 6 hours of curing, sodium polyacrylate reduced the erosion rate to 3.98 g/min, limited the cumulative erosion mass to only 35 g, stabilized the permeability coefficient within the range of 10 ⁻ ⁶ to 10 ⁻ ⁷ cm/s, and shortened the permeability stabilization time to 6.3 minutes. Its improvement effect was superior to that of the other two stabilizers, meeting the anti-seepage requirements for high-standard cut-off walls. The research findings provide efficient and reliable chemical improvement solutions and a theoretical basis for anti-seepage engineering in foundation pits under complex coastal geological conditions.